The emerging roles of ICT in forestry education (An experience of the Faculty of Forestry, Gadjah Mada University, Indonesia) - Susanti, Ari; Hermawan, Taufik Tri (2008)
Faculty of Forestry, Gadjah Mada University was far from ICT custom until the end of 2002. In early 2003, The Faculty was connected to the internet and since then a substantial transformation in ICT utilization for education happened. The internet connection uses fiber optics with capacity up to 100 Mbps. The alteration has been happening in three main businesses of the faculty, namely education, research, and public services. This paper mainly illustrates the revolution in education since ICT has become the substantial means of delivery. Many problems were faced at the beginning of ICT inauguration. Lack of ICT literacy was the main problem in human resources. The lack of ICT literacy makes reluctant response of most lecturers and staffs in the faculty. Another problem is lack of facility and funds which limit the access of lecturers and staffs at the early phase. Supporting policy is the keyword for the success of ICT utilization for education in the faculty. This includes the policy at faculty, university, and national levels. In 2002, the University initiated the internet connection. This policy was followed by the policy in the faculty level which was connected to the internet in early 2003. At the end of 2003, the whole university was connected to the internet and since then the utilization of ICT as a means of education delivery method was stated in the strategic planning of the university. This situation was supported by national policy on Indonesian Higher Education Network (INHERENT) which was issued at the end of 2006. INHERENT is an internet backbone network which connects 32 universities all over Indonesia. Why does forestry education? The forestry education is always connected to forest resources. In Indonesia, forest resources are scattered all over Indonesia. These forest resources need professional foresters to be located in the areas. However, the universities which offer forestry education are mainly located in certain areas (in Java) which are far from forest areas. The needs and the supplies do not meet in this way. ICT was found to be a benefit to link up this supply and need. It has been five years since the Faculty of Forestry introduced ICT in its working environment. There are several achievements and obstacles which are investigated in this paper. Several indicators are presented to illustrate the passage of e-learning and e-working environment in this faculty. These indicators include hardware, human resources, and learning management, and the policy regarding the application of ICT in the learning processes. However, there is a bigger challenge for the ICT application in forestry education in the future. That is to extend the significance of ICT in forestry education processes not only in the national level but also in regional and international levels.